2018
DOI: 10.3390/ijms19051499
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Acetate Fraction from Persimmon (Diospyros kaki) Ameliorates Cerebral Neuronal Loss and Cognitive Deficit via the JNK/Akt Pathway in TMT-Induced Mice

Abstract: This study was conducted to assess the antioxidant capacity and protective effect of the ethyl acetate fraction from persimmon (Diospyros kaki) (EFDK) on H2O2-induced hippocampal HT22 cells and trimethyltin chloride (TMT)-induced Institute of Cancer Research (ICR) mice. EFDK had high antioxidant activities and neuroprotective effects in HT22 cells. EFDK ameliorated behavioral and memory deficits in Y-maze, passive avoidance and Morris water maze tests. Also, EFDK restored the antioxidant system by regulating m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 63 publications
(82 reference statements)
2
36
0
Order By: Relevance
“…The level of ROS was determined by the DCF-DA method [16]. Cells seeded as 1 × 10 4 cells/well ( n = 5) in a 96-well black plate were incubated for 24 h. Vitamin C as a positive control or different concentrations of AEEF were treated to stabilize the seeded cells for 24 h. To confirm the protective effect against H 2 O 2 , every well except for the control was treated with 200 μ M H 2 O 2 for 3 h. Also, to investigate the protective effect against ethanol, every well except for the control was provided with 500 mM ethanol for 24 h after sample treatment for 3 h. Finally, 50 μ M DCF-DA in phosphate buffered saline (PBS) was treated in every well for 50 min to measure intracellular oxidative stress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of ROS was determined by the DCF-DA method [16]. Cells seeded as 1 × 10 4 cells/well ( n = 5) in a 96-well black plate were incubated for 24 h. Vitamin C as a positive control or different concentrations of AEEF were treated to stabilize the seeded cells for 24 h. To confirm the protective effect against H 2 O 2 , every well except for the control was treated with 200 μ M H 2 O 2 for 3 h. Also, to investigate the protective effect against ethanol, every well except for the control was provided with 500 mM ethanol for 24 h after sample treatment for 3 h. Finally, 50 μ M DCF-DA in phosphate buffered saline (PBS) was treated in every well for 50 min to measure intracellular oxidative stress.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was measured by the MTT method [16]. Cells were seeded and pretreated with EFAE or vitamin C in the same manner as the DCF-DA method in a 96-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a treatment with TMT markedly enhanced neurogenesis in the dentate gyrus and olfactory bulb by inducing the proliferation of the endogenous neural stem/progenitor cells (NPCs) in each of these brain regions. 16,17) In rodents, TMT was found to cause hippocampus-dependent cognitive deficits, including short-term memory, as measured in the passive avoidance and novel object recognition testes [18][19][20][21] ; spatial working memory using the modified Y-and radial arm mazes 21,22) ; and spatial long-term memory using the Morris water maze. 21,23,24) Furthermore, behavioral studies demonstrated that TMT induced abnormal behaviors such as locomotor activity or depressive-like behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…16,17) In rodents, TMT was found to cause hippocampus-dependent cognitive deficits, including short-term memory, as measured in the passive avoidance and novel object recognition testes [18][19][20][21] ; spatial working memory using the modified Y-and radial arm mazes 21,22) ; and spatial long-term memory using the Morris water maze. 21,23,24) Furthermore, behavioral studies demonstrated that TMT induced abnormal behaviors such as locomotor activity or depressive-like behaviors. 17,21,25) Therefore, TMT-intoxicated rodents are a useful model of degenerative diseases, such as Alzheimer's disease, the most common cause of dementia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation